Activin signal promotes cancer progression and is involved in cachexia in a subset of pancreatic cancer. Issue 2 (28th January 2015) - Togashi, Yosuke; Kogita, Akihiro; Sakamoto, Hiroki; Hayashi, Hidetoshi; Terashima, Masato; de Velasco, Marco A.; Sakai, Kazuko; Fujita, Yoshihiko; Tomida, Shuta; Kitano, Masayuki; Okuno, Kiyotaka; Kudo, Masatoshi; et al.
Highlights: The plasma activin A level can be a prognostic factor in patents with advanced pancreatic cancer (PC). The activin signal promotes cancer progression via non-SMAD pathways in a subset of PC and might be involved in cachexia. The activin signal might be a novel target for the treatment of PC. Abstract: We previously reported that activin produces a signal with a tumor suppressive role in pancreatic cancer (PC). Here, the association between plasma activin A and survival in patients with advanced PC was investigated. Contrary to our expectations, however, patients with high plasma activin A levels had a significantly shorter survival period than those with low levels (median survival, 314 days vs. 482 days, P  = 0.034). The cellular growth of the MIA PaCa-2 cell line was greatly enhanced by activin A via non-SMAD pathways. The cellular growth and colony formation of an INHBA (beta subunit of inhibin)-overexpressed cell line were also enhanced. In a xenograft study, INHBA- overexpressed cells tended to result in a larger tumor volume, compared with a control. The bodyweights of mice inoculated with INHBA -overexpressed cells decreased dramatically, and these mice all died at an early stage, suggesting the occurrence of activin-induced cachexia. Our findings indicated that the activin signal can promote cancer progression in a subset of PC and might be involved in cachexia. The activin signal might be a novel target for the treatment of PC.